ESSENTIALS OF GERIATRIC NEUROANESTHESIA ([S.l.] : CRC PRESS, 2019)
The book covers topics ranging from basic sciences (developmental changes in neuroanatomy and neurophysiology and effects of neuropharmacology) to special situations such as brain death, ethical issues and palliative care. It discusses various neurological surgical problems and their challenges along with common problems such as Alzheimer's and Parkinson's disease. A section on Pain covers all possible modalities for relieving pain in this patient population followed by the important issue of palliative care. The book addresses the issue of cognition decline, common in this group. The fact that basic sciences are included along with clinical sciences makes it a unique read for the audience.
Clinical anatomy and relationships of the pituitary glandPathology; Clinical presentation of pituitary tumors with aging; Indications for surgery in elderly patients; Anesthetic management; Emergence from anesthesia; Postoperative management; Postoperative analgesia; Conclusion; References; 9. Neurosurgery: Spine surgery; Introduction; Common problems for which spine surgeries are performed in geriatric population; Preoperative assessment; Antiplatelet drugs; Preoperative investigations; Premedication; Type of anesthesia; Regional anesthesia in spine surgery; Postoperative care; References
OCLC-licensed vendor bibliographic record.
Keywords: Geriatric anesthesia; Anesthesia in neurology; MEDICAL / Surgery / General; MEDICAL / General; MEDICAL / Anesthesiology; MEDICAL / Geriatrics